MXene@nitrogen-doped carbon films for supercapacitor and piezoresistive sensing applications. (December 2022) - Chen, Anli; Wang, Chaoying; Abu Ali, Ola A.; Mahmoud, Samy F.; Shi, Yuting; Ji, Yanxiu; Algadi, Hassan; El-Bahy, Salah M.; Huang, Mina; Guo, Zhanhu; Cui, Dapeng; Wei, Huige
Graphical abstract: Highlights: Porous MXene@nitrogen-doped carbon composite (MC) film was obtained. Nitrogen doping improves the electrochemical performance of MC. The porous network increases the ion transport rate and the sensitivity to strain. The assembled symmetric and zinc-ion hybrid supercapacitors display excellent performance. The MC film based sensor shows high sensitivity and long durability. Abstract: A simple strategy is proposed to fabricate MXene@nitrogen-doped carbon (MC) composite film by vacuum filtration followed by annealing. PDA nanospheres serve as spacers, carbon precursor, and nitrogen sources, and meanwhile endow MC with porous networks. Nitrogen doping improves the electrochemical performance of MC, while the porous network increases the ion transport rate and the sensitivity to strain. When assembled into a symmetrical supercapacitor, the device delivers a high energy density of 23.2 μWh·cm −2 at a power density of 317.7 μW·cm −2 . The assembled all-solid-state zinc-ion hybrid supercapacitor delivers a much higher energy density of 61.24 μWh·cm −2 at a power density of 352.76 μW·cm −2 . The MC-based wearable sensor exhibits a sensitivity of 0.21 kPa −1 at a pressure range of 0–2 kPa for piezoresistive sensing with a superior durability over 2000 cycles. This multifunctional MC composite film has promising potentials for the fabrication of energy storage devices and wearable electronics.